2022
DOI: 10.1002/ese3.1210
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of a solar still using magnetic powder as an energy storage medium‐exergy and environmental analysis

Abstract: The use of different energy storage materials can have a high effect on the water productivity of solar desalination. This study evaluates the impact of magnetic powders on modified solar still (MPSS) performance and compares the results with conventional solar still (CSS). Black iron oxide magnetic powder was selected to increase solar radiation absorption. The black iron magnetic powder simultaneously acts as a thermal storage material and a porous absorber medium. The thermal energy stored in the magnetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Various designs of passive and active solar distillers [26] Researchers and scientists have analyzed the impact of magnetic fields on the past water evaporation rate. They found that magnetization strongly affects the rate of water evaporation [43,44,45,46]. Therefore, the magnetic field is one of the most significant and recent techniques affecting the productivity of solar stills.…”
Section: Figurementioning
confidence: 99%
“…Various designs of passive and active solar distillers [26] Researchers and scientists have analyzed the impact of magnetic fields on the past water evaporation rate. They found that magnetization strongly affects the rate of water evaporation [43,44,45,46]. Therefore, the magnetic field is one of the most significant and recent techniques affecting the productivity of solar stills.…”
Section: Figurementioning
confidence: 99%
“…Renewable energy is identified as an alternative source of energy generation because of its abundant nature on earth [4]. Studies have noted the immense potential of solar energy as an option for generating electricity around the world since it is more economically viable, especially for developing countries [5][6][7][8][9]. India is among the leading developing countries where the energy demand rate has grown fast within the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…India is among the leading developing countries where the energy demand rate has grown fast within the last few decades. With a population of around 1.5 billion, nearly 43% of India's population has access to grid-based electricity, while 57% use either non-grid sources for electricity and lighting or do not use any electricity at all [4][5][6]. India intends to address its issues concerning environment and energy through the promotion of renewable energy use and increased efficiency across the country.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Passive solar stills are systems that mainly rely on solar irradiation only to obtain potable water by evaporation. 9 Their productivity is lower and cannot be used for the large-scale productions. According to the geometry of the glass cover, solar still can be categorized into many types such as pyramid type solar still, tubular still, single slope, stepped solar still, cascade solar still and double slope solar still.…”
Section: Introductionmentioning
confidence: 99%